2021
DOI: 10.1186/s13690-021-00696-z
|View full text |Cite
|
Sign up to set email alerts
|

“I don’t know if we’ll ever live in harmony”: a mixed-methods exploration of the unmet needs of Syrian adolescent girls in protracted displacement in Lebanon

Abstract: Background The current crisis in Syria has led to unprecedented displacement, with neighbouring Lebanon now hosting more than 1.5 million conflict-affected migrants from Syria. In many situations of displacement, adolescent girls are a vulnerable sub-group. This study explores and describes the self-reported unmet needs of Syrian adolescent girls who migrated to Lebanon between 2011 and 2016. Methods This mixed-methods study focusing on the unmet n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Barriers were analyzed to identify the strongest themes at each level. From the selected studies, 12 mentioned strong individual level barriers [ 28 – 30 , 34 , 42 49 ], 11 stated barriers at the social and community level [ 28 – 31 , 34 , 42 , 45 , 46 , 48 , 50 , 51 ], 10 mentioned issues related to the institutional and health care level [ 28 , 30 , 31 , 34 , 43 , 46 , 48 51 ], and 9 mentioned structural level barriers [ 28 , 30 , 31 , 45 48 , 50 , 51 ]. In eight studies, we identified all of the four-level barriers to SRH utilization among migrants and refugees.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Barriers were analyzed to identify the strongest themes at each level. From the selected studies, 12 mentioned strong individual level barriers [ 28 – 30 , 34 , 42 49 ], 11 stated barriers at the social and community level [ 28 – 31 , 34 , 42 , 45 , 46 , 48 , 50 , 51 ], 10 mentioned issues related to the institutional and health care level [ 28 , 30 , 31 , 34 , 43 , 46 , 48 51 ], and 9 mentioned structural level barriers [ 28 , 30 , 31 , 45 48 , 50 , 51 ]. In eight studies, we identified all of the four-level barriers to SRH utilization among migrants and refugees.…”
Section: Resultsmentioning
confidence: 99%
“…Lack of female healthcare workers, denial of service based on marital status, discrimination, inhumane treatment, lack of confidence to provide the service, language barrier, and poor skills and policy knowledge were common barriers. Healthcare in turn often complains about burnout and work overload [28,30,43,44,48,50,51].…”
Section: Went Back To Syria To Be Treated " (Young Girl Idi)mentioning
confidence: 99%
“…The development of the interview guide was guided by the published literature review (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(30)(31)(32)(33)(34)(35)(36)(37) on the topic and by consultation with a group of experts that included a psychologist, a sociologist, a family physician, and two schoolteachers. Each consultant was approached by the investigators, provided with the developed tool and requested to provide feedback on the clarity, comprehensiveness, and appropriateness of the questions.…”
Section: Data Collectionmentioning
confidence: 99%
“…Not only can the crisis in Syria exacerbate pre-existing mental disorders within the refugees, but it could also trigger the surfacing of multiple psychosocial problems (14,15). Previous studies have investigated the psychosocial problems and needs among Syrian refugee adolescents (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). However, few studies looked at Syrian adolescents in Jordan (30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%